TULUNGAGUNG-TALANGAGUNG: SOSIAL EKONOMI MASYARAKAT TULUNGAGUNG DALAM MENGHADAPI BANJIR 1955-1986 - Kusairi, Latif (IAIN Surakarta, 2025)
This paper examines the history of flooding in Tulungagung and its mitigation efforts from the colonial period to post-independence. Tulungagung is known as a flood-prone area due to an imbalance between river capacity and abundant water volume. The Dutch colonial government undertook the first mitigation effort through the Vlugter project, which only managed to overcome flooding for a short time. Subsequently, during the Japanese occupation, the Neyama Tunnel project was built using Rōmusha labor, although this resulted in loss of life. After independence, flooding returned with greater intensity, prompting the Indonesian government to implement a third phase of flood mitigation projects, including constructing the South Tulungagung Tunnel and a dam in the Brantas River Basin. In addition to natural factors, forest encroachment by local communities also exacerbated flooding from mountainous areas. These projects transformed flood-prone areas into fertile agricultural land and improved irrigation systems. Ultimately, this ecological and infrastructural transformation positively impacted regional economic growth, making Tulungagung a significant economic center.Keywords: economy, flood, mitigation, Tulungagung.